Teknik budi daya larva Hermetia illucens (Linnaeus) (Diptera: Stratiomyidae) sebagai sumber protein pakan ternak melalui biokonversi limbah loading ramp dari pabrik CPO - Agustin Zarkani; Miswarti Miswarti (Jurnal Entomologi Indonesia, 2012)
Larvae of Hermetia illucens fly (Linnaeus) is an important source of alternative protein and can be used as pellets for feeds. Currently the production of H. illucens larvae is still limited because its rearing depends on palm kernel meal. The objective of the research is to explore alternative media for rearing, i.e. using loading ramp waste from crude palm oil factory. The study was conducted using physical-chemical analysis of the media. Evaluation of potential rearing media of loading ramp was done by studying the suitability of loading ramp fermented by EM4®, rumen microbes, and organic liquid fertilizer and without fermentation. Treatment media was develop with an enrichment ratio of 1 : 0.25, 1 : 05, and 1 : 1 (v/v) for bran and husk, and 1.25, 2.5, and 5% (w/w) for coconut sugar. Each experiment was arranged in complete randomized design using 20 larva of the 2nd instar. Larvas were incubated in plastic with tube with diameter of 10 cm and 20 cm in height containing of media 300 g. Response differences in growth and mortality were analyzed by ANOVA and least significant differences test at 0.05 levels. Preference and analysis suitability of the media were conducted using material enrichment. Results show that the loading ramp waste contain 9.80% protein and 10.32% fat. Although the media are could support growth and development of the larvae at different degree, media from waste fermentation POC loading ramp with bran enrichment 1 : 0.5 (v/v) is the best media for rearing larva.